2011
DOI: 10.1177/1748048510386747
|View full text |Cite
|
Sign up to set email alerts
|

Communicating business greening and greenwashing in global media: A multimodal discourse analysis of CNN’s greenwashing video

Abstract: This article explores how knowledge about business greening and greenwashing is communicated in the specialized discourse of CNN's Greenwashing video. Drawing upon a social semiotic approach, the article proposes a model of multimodal discourse analysis to explore how processes of knowledge selection are employed for shaping public awareness and understanding of environmental issues in the context of the greening or greenwashing efforts of businesses. Furthermore, the article discusses how environmental busine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Specifically, critical analyses of the media’s “greenwashing” and branding of the environmental movement in text and image have helped reveal the ideological work behind these media messages. Maier (2011) and Hansen and Machin (2008) noted in their respective studies that sustainability discourses in mass media benefited individuals or groups already in positions of power. In so doing, they upheld the status quo and marginalized challenges to entrenched power and ways of life.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specifically, critical analyses of the media’s “greenwashing” and branding of the environmental movement in text and image have helped reveal the ideological work behind these media messages. Maier (2011) and Hansen and Machin (2008) noted in their respective studies that sustainability discourses in mass media benefited individuals or groups already in positions of power. In so doing, they upheld the status quo and marginalized challenges to entrenched power and ways of life.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Vaara et al, 2006). Analysts have taken up these frameworks in a number of different case studies, including studies of education materials (Van Leeuwen, 2007), news media (Fitzgerald and O’Rourke, 2016; Maier, 2011; Vaara et al, 2006; Vaara and Tienari, 2008), political cartoons (Mazid, 2008), political speeches (Oddo, 2011; Reyes, 2011; Rojo and Van Dijk, 1997), and visa applications (Van Leeuwen and Wodak, 1999). Here, I apply it in a study of tourism promotional literature.…”
Section: Forms Of Legitimationmentioning
confidence: 99%
“…It allows images and texts to share space without granting primacy to one over the other. Scholars have found social semiotics a useful tool for exploring a broad range of multimodal discursive practices including the media's coverage of 'greenwashing ' (Maier, 2011) and branding of the environmental movement in text and images (Hansen & Machin, 2008). Both of these studies explored sustainable discourse as presented through text and image, revealing the sustainability discourse was constructed in a way to benefit individuals or groups in a position of power.…”
Section: It the Connection Between Discourse And Ideology That Is Cenmentioning
confidence: 99%
“…The discourse of sustainability shows how discursive limits are constantly set, challenged, shifted and adapted based on contextual and social factors. The emphasis on the environmental aspect of sustainability has led to significant research on the discursive practices of various media concerning the subject (Alexander, 2009;Delmas & Burbano, 2011;Hansen & Machin, 2008;Hepburn, 2013;Maier, 2011;Mühlhäusler & Peace, 2006). The critical approaches of these studies revealed a complex discourse with a myriad of voices contributing to its production.…”
Section: It the Connection Between Discourse And Ideology That Is Cenmentioning
confidence: 99%